ChemInform Abstract: Recent Progress in Sustainable Polymers Obtained from Cyclic Terpenes: Synthesis, Properties, and Application Potential. Issue 42 (October 2015) - Winnacker, Malte; Rieger, Bernhard
Abstract Review: [131 refs.